2004
DOI: 10.1080/01449290310001659213
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multimodal feedback on older adults' task performance given varying levels of computer experience

Abstract: This experiment examines the effect that computer experience and various combinations of feedback (auditory, haptic, and/or visual) have on the performance of older adults completing a drag-and-drop task on a computer. Participants were divided into three computer experience groups, based on their frequency of use and breadth of computer knowledge. Each participant completed a series of drag-and-drop tasks under each of seven feedback conditions (three unimodal, three bimodal, one trimodal). Performance was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…The sample is therefore not representative of the general population. As recruitment was on a voluntary basis, these results were anticipated, as an interest in computers has been found to correlate with increased experience in the use of computers (Albert, 1987, Jacko et al, 2004. Albert (1987) also found these factors to be related to socioeconomic status and computer confidence though these were not directly assessed in this study.…”
Section: Discussionmentioning
confidence: 60%
“…The sample is therefore not representative of the general population. As recruitment was on a voluntary basis, these results were anticipated, as an interest in computers has been found to correlate with increased experience in the use of computers (Albert, 1987, Jacko et al, 2004. Albert (1987) also found these factors to be related to socioeconomic status and computer confidence though these were not directly assessed in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Systems and interfaces use various types of feedback as part of their design. Jacko et al (2004) found that both novice and experienced older users can benefit from improved feedback combinations more significantly than the younger user groups. Although the experienced user performed well with drag and drop tasks, they also benefited from multimodal feedback.…”
Section: Age-related Interface Issuesmentioning
confidence: 94%
“…However, previous research also suggests an advantage of auditory haptic over visual haptic feedback for older users executing simple movement tasks (e.g. drag and drop) (Jacko et al, 2004).…”
Section: Older and Younger Usersmentioning
confidence: 98%